Burnout, coping and suicidal ideation: An application and extension of the job demand-control-support model. (3rd April 2017) - Wallace, Jean E.
ABSTRACT: Suicidal tendencies are typically considered related to individual traits or predispositions, but some occupations have significantly higher rates than other occupations and the general population. This article proposes that stressful work conditions may be important in understanding occupational variations in suicidal tendencies. It explores the links between work-related factors and burnout, and suicidal thoughts among veterinarians. Burnout appears to be an important mediator in understanding veterinarians' suicidal tendencies; work conditions that are emotionally exhausting for veterinarians may foster suicidal thoughts. Individual coping strategies are also explored. Emotion-focused strategies of avoidance and alcohol consumption not only exacerbate burnout and suicidal thoughts but also amplify the harmful effects of some job demands. Active problem solving is not as beneficial as expected, but a supportive work environment is a valuable coping resource. Organizational interventions and coping resources effective in reducing burnout may also reduce the risk of suicide for those in service occupations.